Factors Related to Herbal Medicine Use in Breastfeeding Mothers in Klaten Regency, Indonesia - Sayuti, Nutrisia Aquariushinta; Atikah, Nur (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2024)
Background: The diverse plant diversity promotes herbal medicine use for breastfeeding mothers in Klaten to promote postpartum health and breast milk production. However, factors related to herbal medicine use have not yet been studied.Objectives: The study aimed to identify factors related to herbal medicine use among breastfeeding mothers in the Klaten Regency.Methods: The study used a structured survey questionnaire in a cross-sectional approach. Survey participants were recruited from community health centers in Klaten. The survey instrument was validated questionnaires that consisted of predisposing, supporting, and need factors. Logistic regression analyzed factors related to herbal medicine used in breastfeeding mothers.Results: The survey of 111 breastfeeding mothers in Klaten Regency found that 78.40% of respondents used herbal medicine, with most aged 20-35. The most perceived health status of the mother and breastfed child was healthy. Most respondents agreed that herbal medicine was safer and more effective than conventional medicine. The logistical regression revealed that breast milk flow issues (p-value = 0.000) and the belief that herbs are more effective than chemical medications (p-value = 0.008) significantly influence the use of herbal medicine.Conclusion: The study concluded that the significant factors related to herbal medication use were breast milk's smoothness and the belief that herbal medicine is more efficacious than conventional medicine. The belief is often shaped by social culture and family experiences, leading to the possibility of incorrect information. Health professionals are crucial in providing information about herbal medicine and recommending its use to promote health and prevent health problems.